Community Knowledge Enhancement in Waste Management for a Healthy Environment Through the "Benderang Sentosa" Program - Sulistyono, R. Endro; Artiani, Nanda Ayu; Bezariani, Calista Safa (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Waste management remains a critical issue related to environmental health. Insufficient knowledge in waste management contributes to environmental degradation, including soil, water, and air pollution, and serves as a potential source of diseases. This community service initiative aimed to implement the "Benderang Sentosa" Waste Management Program to enhance community knowledge of waste management practices. The program involved health education and training sessions conducted three times over three weeks. A total of 60 school-age children and 50 health cadres participated. Community knowledge was assessed using a pre-developed questionnaire. Descriptive data were analyzed to compare pre- and post-intervention results. The main result shows that the knowledge level of health cadres about waste management increased by 76%. Similarly, 75% of school-age children demonstrated a significant improvement in their understanding of waste management. The "Benderang Sentosa" Waste Management Program effectively increased community knowledge, contributing to better waste management practices and supporting the goal of a healthier environment.